Coworker relations and incentive schemes - Teo, Erica Yan Ting (2019)
In the workforce, when seen from an economic theory perspective, managers’ main aim is to maximise the firms’ profits. However, they have no idea whether workers act in their best interests. Therefore, managers need to think about how to utilise different incentive schemes to elicit effort and truthful reporting of workers’ performance with minimal cost. We discover that coworker relations not only have implications on the productivity in workplaces, it is also an important attribute for the cost and effectiveness of incentive schemes. This paper develops a principal-two-agent model where output is affected by the agents’ joint effort level as well as the quality of their relationship. Our model takes into consideration two different relationship parameters: r1 which affects output and r2 which affects the worker’s utility. The results show that manager’s profit increases with r1 and decreases with r2. We also discover that with a more intensive coworker relations, peer evaluation bonus can incentivise effort. In line with this, the optimal contract always includes a peer evaluation bonus. However, peer evaluation may become costly and less accurate with increasing intensity of coworker relations. Hence, at times, the optimal contract may be a combination of peer evaluation and output bonus.